The Completeness of Articles and Citation Analysis on the Slovenian Wikipedia - Manca Noč; Maja Žumer (Knjižnica, 2012)
ABSTRACT Purpose: The purpose of this research was to examine the number and type of sources cited by featured articles on the Slovenian Wikipedia and to compare a sample of featured articles with a sample of random articles, with the purpose of determining an indicative framework for the quality of both. Methodology: 122 featured Wikipedia articles created in 2009, 2010 and 2011 were analysed, particularly the topic and originality of an article and the number, language and type of sources. A sample of featured articles was compared to a sample of 194 random articles which represent average Wikipedia articles. Results: The results showed that most of the featured articles were adapted from the English Wikipedia, the most common topics being natural science, sports and history. It turned out that the majority of random articles were stubs and articles with a minimal number of references, with military, sports or biographic topic. Based on these results it has been confirmed that despite their deficiencies the featured articles represent the highest-quality Wikipedia articles as compared to random articles. Research limitation: The biggest limitation of the research was the very low quality of random articles as they were mostly stubs, so it was hard to even determine sensible parameters upon which they could be analysed. Originality/practical implications: This is the first research of the Slovenian Wikipedia that focuses on citation analysis of featured articles. Results of this research offer valuable information to editors of featured articles on their own work as well as point out certain deficiencies which can be eliminated.